Neuroimaging Correlates of Depression—Implications to Clinical Practice - Castanheira, Lígia; Silva, Carlos; Cheniaux, Elie; Telles-Correia, Diogo (Frontiers in Psychiatry, 2019)
The growth of the literature about neuroimaging of Major Depression Disorder (MDD) over the last several decades has contributed to the advances in the identification of specific brain regions, neurotransmitter systems, and networks associated with depressive illness. However, fundamental questions about the pathophysiology and etiology of MDD persist. The authors did a non-systematic review of the literature using PubMed database, with the search terms: "major depressive disorder", "neuroimaging", "functional imaging", "magnetic resonance imaging", "functional magnetic resonance imaging" and "structural imaging", being selected the significant articles published on the topic. The brain regions that are most affected across the studies are the orbitomedial prefrontal cortex, anterior cingulate cortex, amygdala, hippocampus, cerebellum, and the basal ganglia. These regions interact with particular neurotransmitter systems, neurochemicals, hormones, and other signal proteins, even more, the evidence supports an altered fronto-limbic mood regulatory circuitry in MDD patients. Despite the positive findings, translation to treatment of MDD remains illusory. In conclusion, this article aims to be a critical review of the neuroimaging correlates of depression in clinical research with the purpose to improve clinical practice.